2020
DOI: 10.1080/02713683.2019.1697453
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complexity of retina and pluripotent stem cell derived retinal organoids with single cell RNA sequencing: current progress, remaining challenges and future prospective

Abstract: Single-cell sequencing technologies have emerged as a revolutionary tool with transformative new methods to profile genetic, epigenetic, spatial, and lineage information in individual cells. Single-cell RNA sequencing (scRNA-Seq) allows researchers to collect large datasets detailing the transcriptomes of individual cells in space and time and is increasingly being applied to reveal cellular heterogeneity in retinal development, normal physiology, and disease, and provide new insights into cell-type specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 129 publications
(146 reference statements)
0
27
0
Order By: Relevance
“…For RGCs derived from human iPSCs, attempts have been made to explore RGC subtype diversity within the organoids themselves by single-cell RNA-seq, though, until recently, attempts along those lines were hindered by the lack of appropriate reference datasets and sample numbers remained low, limiting conclusions. 49 , 56 , 57 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…For RGCs derived from human iPSCs, attempts have been made to explore RGC subtype diversity within the organoids themselves by single-cell RNA-seq, though, until recently, attempts along those lines were hindered by the lack of appropriate reference datasets and sample numbers remained low, limiting conclusions. 49 , 56 , 57 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…Such condition-specific zero-inflation is commonly used in a number of popular software packages [33] , [20] , [25] , [16] , [27] . Moreover, the zero-inflated model we use here has been used in multiple studies to conduct differential expression analysis [50] , [51] , [52] , [53] . We refer to these two models respectively as the Zero-Inflated Negative Binomial (ZINB) and Negative Binomial (NB) models (see Section 6 for more details).…”
Section: Real Data Examplesmentioning
confidence: 99%
“…However, faithfulness of subtype diversification, molecular marker expression within subtypes and relative proportions of various types are still largely missing. Several recent studies took advantage of the advances in single‐cell transcriptional profiling to fill this gap 21,79‐82 . First studies with a relatively small number of cells demonstrated robust specification into photoreceptors and Müller glia 21,79 .…”
Section: Emerging Technologies For the Analysis Of Retinal Organoidsmentioning
confidence: 99%